Finnish diabetes risk score (findrisc) for type 2 diabetes screening compared with the oral glucose tolerance test: A systematic review and meta-analysis of diagnostic test accuracy - Acosta-Reyes, Jorge; Rodríguez Garrido, Diana Patricia; Acosta Vergara, Tania; Aschner, Pablo; Fraga, Cristina Alejandra; Vazquez-Fernandez, Aitana; Tuomilehto, Jaakko; Gabriel, Rafael (Diabetes research and clinical practice, 2025)
to determine the accuracy of the FINDRISC score compared with the oral glucose tolerance test for the detection of type 2 diabetes (T2D). This systematic review and meta-analysis involved electronic search in: Embase, Scopus, Medline, WoS, and Cochrane, from inception to November 2024. QUADAS-2 was employed to assess the risk of bias, and the certainty of evidence with the GRADE approach. A bivariate hierarchical random effects model was performed and the sensitivity, specificity, and their 95% confidence intervals (CI) along with the summary ROC curve, were calculated. 25 cross-sectional studies and 7 cohort studies were included. The individual FINDRISC cut-off between 9 and 15 points was analysed. The AUC ranged between 0.694 and 0.755, sensitivity between 53.1% (95% CI 38.9–66.8) and 84.7% (95% CI 72.7–92.0), while the false positive rate (FPR) ranged from 21.8% (95% CI 12.9–34.3) to 54.8% (95% CI 38.0–70.5). The FINDRISC scores of 9 and 10 points show the best effectiveness for screening T2D, with moderate and low quality of evidence respectively. Although the cut-off of 12 points has lower sensitivity, it significantly reduces the FPR and increase the specificity with moderate quality of evidence. Private institutional own resources. PROSPERO (CRD42020189768).